Optimized design of substrate-integrated hollow waveguides for mid-infrared gas analyzers - Fortes, Paula Regina; Silveira Petruci, Joao Flavio da [UNESP]; Wilk, Andreas; Cardoso, Arnaldo Alves [UNESP]; Raimundo, Ivo Milton; Mizaikoff, Boris (Iop Publishing Ltd, 2014)
Design and analytical performance studies are presented for optimizing a new generation of hollow waveguides suitable for quantitative gas sensing-the so-called substrate-integrated hollow waveguide (iHWG). Taking advantage of a particularly compact Fourier transform infrared spectrometer optimized iHWG geometries are investigated toward the development of a multi-constituent breath analysis tool compatible for usage, e.g., in exhaled mouse breath analysis. Three different iHWG geometries were compared, i.e., straight, meandering one-turn and meandering two-turn waveguide channels aiming at maximizing the related analytical figures-of-merit including the achievable limits of detection for selected exemplary analytes. In addition, efficient coupling of infrared (IR) radiation into straight iHWGs was investigated using integrated optical funnel structures. Calibration functions of butane in nitrogen serving as IR-transparent matrix gas were established and compared for the various iHWG geometries. Given the tidal volume of exhaled breath (EB) samples ranging from a few hundreds of milliliters (human, swine) to a few hundreds of microliters (mouse), it is essential for any given analysis to select an appropriate waveguide geometry and volume yet maintaining (i) a compact footprint ensuring hand-held instrumentation, (ii) modular exchange of the iHWG according to the analysis requirement yet with constant device format, and (iii) enabling inline/online measurement capabilities toward continuous EB diagnostics.
Keywords: substrate-integrated hollow waveguide; mid-infrared; mid-infrared sensors; optical sensors; gas sensing; hydrocarbons